A novice academics’ reflections on the implementation of proctored examinations: An auto-ethnographic account - Methi, L. M. (South African Journal of Higher Education, 2023)
The study reflects on the challenges I, as the researcher, experienced during the implementation of proctored examinations as a novice academic in a higher education institution (HEI). Through self-reflection, I explored and critiqued my biases, preferences, perceptions and preconceptions, as I navigated proctored examinations as an academic and how they impacted my well-being and resilience. Auto-ethnography was used as the qualitative research design to explore and critique my transformational experiences. Auto-ethnography is experience-based, explores only one problem and it is not continual. The nature, extent, and significance of emotions I experienced were recorded in the form of e-mails, Microsoft teams meeting recordings and data relating my emotions and any other reflections were shared/expressed in my interaction with colleagues. I retrospectively and selectively wrote in my journal about “epiphanies” that I perceived to have significantly impacted my performance and the ultimate results of students. I used constructivist grounded theory principles to analyse my reflections and found that the challenges stemmed from a lack of preparedness, impulsive skilling process in facilitating a proctored examination, increased emotionality, and depletion of collaboration as potential risks. The process provided me with new ways of understanding what it means to learn and function during a time of disruptive change. Ensuring and maintaining academic honesty and integrity in any learning environment is vital and significant and requires educational innovation that replaces existing methodologies and modes of knowledge transmission, by providing new alternatives for teaching, learning and assessment. The authors’ focus might be secondary in the minds of many social scientists who are directly contributing to our understanding of novice academics experiences in implementing the proctored examination. However, despite some limitations and ethical concerns, I urge qualitative researchers to embrace the focus on the adaptation-based approach to the resilience of novice academics in the implementation of proctored examinations.